Retrospective analysis of factors influencing the implementation of a program to address unprofessional behaviour and improve culture in Australian hospitals - Kate Churruca; Johanna Westbrook; Kathleen L Bagot; Ryan D McMullan; Rachel Urwin; Neil Cunningham; Rebecca Mitchell; Peter Hibbert; Neroli Sunderland; Erwin Loh; Natalie Taylor (BMC, 2023)
Abstract Background Unprofessional behaviour among hospital staff is common. Such behaviour negatively impacts on staff wellbeing and patient outcomes. Professional accountability programs collect information about unprofessional staff behaviour from colleagues or patients, providing this as informal feedback to raise awareness, promote reflection, and change behaviour. Despite increased adoption, studies have not assessed the implementation of these programs utilising implementation theory. This study aims to (1) identify factors influencing the implementation of a whole-of-hospital professional accountability and culture change program, Ethos, implemented in eight hospitals within a large healthcare provider group, and (2) examine whether expert recommended implementation strategies were intuitively used during implementation, and the degree to which they were operationalised to address identified barriers. Method Data relating to implementation of Ethos from organisational documents, interviews with senior and middle management, and surveys of hospital staff and peer messengers were obtained and coded in NVivo using the Consolidated Framework for Implementation Research (CFIR). Implementation strategies to address identified barriers were generated using Expert Recommendations for Implementing Change (ERIC) strategies and used in a second round of targeted coding, then assessed for degree of alignment to contextual barriers. Results Four enablers, seven barriers, and three mixed factors were found, including perceived limitations in the confidential nature of the online messaging tool ('Design quality and packaging'), which had downstream challenges for the capacity to provide feedback about utilisation of Ethos ('Goals and Feedback', 'Access to Knowledge and Information'). Fourteen recommended implementation strategies were used, however, only four of these were operationalised to completely address contextual barriers. Conclusion Aspects of the inner setting (e.g., 'Leadership Engagement', 'Tension for Change') had the greatest influence on implementation and should be considered prior to the implementation of future professional accountability programs. Theory can improve understanding of factors affecting implementation, and support strategies to address them.